Fuzzy cognitive map-based reasoning for prediction of multi-stage attacks in risk assessment. (2016) - Sarala, R.; Zayaraz, G.; Vijayalakshmi, V.
The knowledge and sophistication with which attacks are carried out in recent times, makes it essential for the organisations to carry out risk assessment in a proactive manner in order to reduce the risk impact. Multi-stage attacks are a form of complex attacks which target more than one computer in a network to carry out an attack. In order to have an effective risk management the multi-stage attacks that occur in multiple steps also need to be considered. To predict the multi-stage attacks the causality between the steps in the execution of the attack need to be modelled which can be done using fuzzy cognitive maps. Fuzzy cognitive maps can serve as a reasoning tool as they provide the fuzzy degree of causation between the events. The proposed system makes use of fuzzy cognitive maps to model the causally dependent events to predict multi-stage attacks.